DEVELOPMENT OF INTERACTIVE LEARNING MEDIA USING THE LUMIO PLATFORM FOR ALGEBRA MATERIAL ON STUDENT'S MATHEMATICAL CONCEPT UNDERSTANDING ABILITY - Karomah, Fitria; Novaliyosi; Maman Fathurrohman (EMTEKA: Jurnal Pendidikan Matematika, 2025)
This research is motivated by the difficulties experienced by students in understanding mathematical concepts in algebra materials, lack of student interest in learning, and limited use of learning resources. To overcome this, the researcher provide to develop interactive learning media using the Lumio platform in algebra materials to help students' ability to understand mathematical concepts. The results of the development measured are in the form of validity and practicality. Type of this study is Research and Development (R&D) by carrying out the development stages of ADDIE, namely analysis, design, development, implementation, and evaluation. The sample of this study is 7th grade students in one of the junior high schools in Serang City. The research instruments used included teacher interview sheets, expert validation questionnaires, and response questionnaires. The data analysis techniques used are qualitative descriptive and quantitative descriptive. This research produced a product in the form of interactive learning media using the Lumio platform on algebraic material. The results of the validation of interactive learning media earned a percentage of 89% from material experts, 89% from education experts, and 86% from media experts. The results of the response of teacher and students to interactive learning media earned a percentage of 85% from teacher and 74% from students. Thus, this study shows that the development of interactive learning media using the Lumio platform is declared valid and practical to be used in helping students' ability to understand mathematical concepts, especially in algebra materials.